Response of male adult Aedes mosquitoes to gamma radiation in different nitrogen environments - Bimbilé Somda, Nanwintoum Séverin; Yamada, Hanano; Kraupa, Carina; Mamai, Wadaka; Maiga, Hamidou; Kotla, Simran Singh; Wallner, Thomas; Martina, Claudia; Bouyer, Jeremy (Frontiers in Bioengineering and Biotechnology, 2022)
The developmental stage of the mosquito is one of the main factors that affect its response to ionizing radiation. Irradiation of adults has been reported to have beneficial effects. However, the main challenge is to immobilize and compact a large number of adult male mosquitoes for homogenous irradiation with minimal deleterious effects on their quality. The present study investigates the use of nitrogen in the irradiation of adult Aedes albopictus and Ae. aegypti. Sample irradiation in nitrogen (N2), and in air after being treated with nitrogen (PreN2) were compared with irradiation in air, at gamma radiation doses of 0, 55, 70, 90, 110, and 125 Gy. In both species, nearly 0 % of egg hatch rate was observed following doses above 55 Gy in air versus 70 Gy in PreN2 and 90 Gy in N2. Males irradiated at high mosquito density induced similar egg hatch rates as at low density. Nitrogen treatments showed beneficial effects on the longevity of irradiated males for a given dose revealing the radioprotective effect of anoxia. However, irradiation in N2 or PreN2 slightly reduced the male flight ability. Nitrogen treatment was found to be a reliable method for adult mosquito immobilization. Overall, these results demonstrated that nitrogen may be useful in adult Aedes mass-irradiation. The best option seems to be the PreN2 since it reduces the immobilization duration and requires a lower dose than the N2 environment to achieve full sterility but with similar effects on the male quality. However, further studies are necessary to develop standardized procedures including containers, time and pressure for flushing with nitrogen, duration of immobilization considering mosquito species, age, density, and the possibility to restore the quality of the sterile males.